Implementation of the Gallery of Learning Strategy in Fiqh Instruction at Madrasah Ibtidaiyah - Neneng Bayjura Harun; Vian Hanes Andreastya (Journal Of Islamic Education And Pesantren, 2024)
This study aims to analyze the implementation of the Gallery of Learning strategy in Fiqh instruction at Madrasah Ibtidaiyah and its relationship to students’ learning motivation and engagement. The research employed a qualitative approach using a case study design conducted in a fifth-grade class of a Madrasah Ibtidaiyah. Data were collected through participant observation, interviews with teachers and students, and documentation of instructional materials and evaluation results. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing, with triangulation techniques applied to ensure the validity and credibility of the findings. The results indicate that the implementation of the Gallery of Learning strategy was conducted through three main stages: group-based lesson planning, the execution of student work exhibitions and gallery rotations, and evaluation through reflection and intergroup discussions. This strategy encouraged active student participation through the creation of visual media, presentations, and collaborative interaction. Its impact was reflected in increased confidence in expressing opinions, greater enthusiasm, and higher levels of student engagement in understanding Fiqh material contextually. In addition to strengthening conceptual understanding, the strategy also fostered intrinsic motivation through interactive, communicative, and meaningful learning experiences. Therefore, Gallery of Learning can serve as an effective alternative strategy for creating participatory and contextual Fiqh learning in Madrasah Ibtidaiyah.